The integrated management plan for Segara Anakan-Cilacap, Central Java, Indonesia. (Manila, Philippines ICLARM, 1992)
ASEAN/US Coastal Resources Management Project, Directorate General of Fisheries, Indonesia
Keywords: Coastal zone management